Positive Identity as a Positive Youth Development Construct: A Conceptual Review - Sandra K. M. Tsang; Eadaoin K. P. Hui; Bella C. M. Law (The Scientific World Journal)
Identity is a core construct in psychology because it refers to how a person addresses issues dealing with who that person is. Important theorists studying the concept of identity, like Erikson, Marcia, and Higgins, assert that identity is organized,is learned, and is dynamic, and a subjective evaluation of an individual’s identity has emotional consequences for that individual. Adolescents who can cultivate a clear and positive identity after their developmental struggles during adolescence often advance more smoothly into adulthood. This paper reviews literature on the nature and structure of identity and examines its importance on adolescent developmental outcomes. It traces significant determinants of identity and proposes strategies for cultivation of positive identity. Observations on current research gaps in the study of identity and future research directions will also be discussed.